LITERATURE REVIEW : Hubungan Kekuatan Otot Tungkai Terhadap Keterampilan Menendang Bola Pada Pemain Sepak Bola - Agis Ardiani (2020)
LITTERATURE REVIEW : CORRELATION BETWEEN LEG STRENGTH MUSCLE WITH SKILL KICKING ON FOOTBALL PLAYERS Agis Ardiani Abstract Leg muscle strength contributes to the final result of the kick, because a good kick will aim at the target, it is made from legs that have qualified muscle strength to balance body position. The purpose of the literature review is to analyze and also examine the research that has been done Previously, the relationship between leg muscle strength and kicking skills at soccer players. The method used is a traditional library review, which analyzes completely, critically, and objectively related to knowledge about certain topics that do not have specific methods in library search strategies. A total of 6 articles were reviewed by the authors and show results that show the relationship of leg strength to soccer kicking skills in soccer players. This was then concluded through the results of the review of the quality of the article itself through Sinta (science and technology index) and using the level of internal validity with a minimum category of B (limited) score based on critical assessments. Keywords: Leg muscle strength, Kicking, Leg muscle strength and kicking, Leg muscle strength and kicking ball, Leg muscle or Shooting.